PENERAPAN MODEL SIKLUS BELAJAR ( LEARNING CYCLE 5E) DENGAN CATATAN TERBIMBING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR FISIKA SISWA DI SMPN 11 JEMBER KELAS VIIB TAHUN AJARAN 2011/2012 - Mustangin - (FKIP Universitas Islam Jember, 2014)
Physics is an adaptive lesson that gives students basic knowledge of natural law. Some of students in junior high school and senior high school think that physics is not fun lessons because the process of physics learning in school the theacher just give formula to remember not the right physics concept. Learning about physics should give direct experince to develop science knowledge and understand surrounding natural scientifically. One of the physics learning activities supposed to meet that is learning cycle 5E with guide note. Learning cycle 5E with guide note focused on improving students’ motivation . After administering this learning cycle 5E with guide note method, the result is (1) improving students’ activity (2) improving students’ achievement of the VII B grade of State Junior High School 11 Jember at the 2011/2012 academic year. Key words: Learning cycle, Guide Note